Avaliação histológica, histomorfométrica, imunohistoquímica e sistêmica do reparo ósseo em defeitos tratados com alendronato ou paratormônio - Deliberador, Frederico Ribeiro (2017)
Deliberador F.R. Histological, histomorphometric, immunohistochemical and systemic evaluation of osseous repair in defects treated with alendronate or paratormonium. Curitiba: Universidade Positivo; 2016. Bisphosphonates (BFs) are drugs that act directly on osteoclasts, inhibiting their reabsorption function, in addition to enhancing the proliferation and maturation of osteoblasts. Parathyroid hormone (PTH) is a hormone secreted by the parathyroid gland that stimulates osteolytic (bone crystal-destroying) activity of osteoclasts and osteocytic osteolysis (reabsorption of calcium and phosphate in bone not yet mineralized). This work aims to demonstrate the effects of local application or imbibition, of BFs and PTH, on the tissue repair of bone defects. A total of 25 male rats were divided into 5 groups: Group C (control), Group B1 (imbibition with biphosphonate solution, 3mg / kg), group B2 (local application of bisphosphonate, 1mg / kg), Group P1 Parathyroid hormone, 20mcg) and Group P2 (local application of parathyroid hormone solution, 20mcg). A bone defect was created in the frontoparietal region. The removed bone was particulate, heavy and placed back in the same position. In Group B1 and P1, the bone removed and particulate was soaked for 3 minutes in these drugs and repositioned in the region of the bone defect. In group B2 and P2, the region of the defect, already grafted, underwent local application of bisphosphonate or parathyroid hormone once a week for 2 months. The animals were euthanized in 8 weeks. The bone blocks, liver, kidneys and encephalon were removed and sent for analysis. In the histological analysis, the groups P1 and P2 presented exuberant angiogenesis with little inflammatory infiltrate. Group B1 and B2 presented great bone neoformation. In the histomorphometric evaluation, with regard to bone neoformation, there was no statistical difference when comparing the groups (p> 0.05) / Anova one-way. In the systemic evaluation, hepatic steatosis was found in group B1 and dystrophic calcification in the encephalon of group P1. There were no changes in the kidneys when compared to the control group.